Thinking with Diagrams: The Chaîne Opératoire and the Transmission of Technical Knowledge in Chinese Agricultural Texts. Issue 2 (1st June 2020) - Bray, Francesca
Abstract: Diagrams make wonderful templates for technical action. It follows that for scholars of science and technology they are both an object and a tool of study. The author explores this relationship in the first part of the article, focusing on one particularly effective format for communicating or retrieving complicated technological sequences: the chaîne opératoire, or procedural sequence. Today we usually think of a diagram as a graphic, but diagrammatic thinking is also frequently expressed in other forms, including text or hybrids of graphics and text. To illustrate this, the author compares the formulation and use of chaînes opératoires in two canonical Chinese agricultural treatises. The Qimin yaoshu ( Essential Techniques for the Common People ) by Jia Sixie, completed ca. 540 CE, was composed before printing was available and makes no use of graphics. The Nongshu ( Agricultural Treatise ) of 1313, authored by Wang Zhen, was published using woodblock print, a medium that facilitated Wang's copious use of graphics. The comparison between these classic treatises invites reflection on how the material techniques of inscription available to an author might influence their diagrammatic thinking. But the chaîne opératoire is good to think with at a more general level too. For historians, the matches or discrepancies between the chaîne opératoire they might draw up to map a technical operation, and the versions that they find in historical sources, suggest ways to think both about technology as a total social fact, and about differences between cultures of communication.